ANALISIS PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MANAJEMEN SEKOLAH DI SD NEGERI 37 PEKANBARU - Juwipa Hardila; Zariul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to describe the role of the principal in improving school management at SD Negeri 37 Pekanbaru. The research subject was the principal of SD Negeri 37 Pekanbaru. The type of research used is qualitative research. The data analysis technique used is Miles and Huberman which uses three stages, namely data reduction, data presentation and verification/drawing conclusions. The research data were obtained from interviews and observations and then elaborated, synthesized, compiled, chose which ones were important and made conclusions. The results of this study are that the role of the principal in improving management at SD Negeri 37 Pekanbaru is carried out properly and to the maximum extent possible. This can be proven by using analysis data on school management at SD Negeri 37 Pekanbaru.Key Words: The role of the principal, school management